Application of Cow Compost and Sago from Charcoal on The Growth of Sawy (Brassica juncea L.) - Diana Susanti,; Nemo Alexia A,; Resubun Mariana L,; Rangga Kusumah,; Nurhaya J. Panga, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to examine the effect of the combined treatment of sago midrib charcoal planting media with different dose levels of cowshed compost on the growth of mustard plants. The study was conducted in Mandala Village, Merauke Regency from February 2022 to March 2022 using a factorial Randomized Block Design with 12 treatment combinations and 4 replicates, namely: A1B1 (soil without cow manure compost), A1B2 (soil + 5 tons of cow manure compost/ ha) A1B3 (soil + cowshed compost 10 tons/ha), A1B4 (soil + cowshed compost 15 tons/ha), A2B1 (soil + sago midrib charcoal without cowshed compost), A2B2 (soil + sago charcoal + compost cowshed 5 tons/ha), A2B3 (soil + charcoal from sago fronds + compost from cowshed 10 tons/ha), A2B4 (soil + charcoal from sago leaves + compost from cowshed 15 tons; ha), A3B1 (sago midrib charcoal without compost cattle), A3B2 (charcoal + 5 ton/ha cowshed compost), A3B3 (sago frond charcoal + 10 ton/ha cowshed compost), A3B4 (sago frond charcoal + 15 ton/ha cowshed compost). The results showed that the combination of the treatment of planting media and cowshed compost had a significant and very significant effect on the A1B4 treatment (soil medium + 15 ton/ha cowshed compost dose) on parameters of plant height (39.75 cm), leaf length at 40 Hst (226.25 mm) and total harvested weight (72 grams). Furthermore, the A2B3 treatment combination (soil medium + sago frond charcoal + 10 tons/ha cowshed compost) showed significantly different yields on the number of leaves parameter (9.75) and the A2B4 treatment (soil medium + sago palm charcoal + 15 cowshed compost) ton/ha) on leaf width parameter (122.75 mm).